Conversor CA/CC com capacitor chaveado para LEDs de potência - Miranda, Pedro Henrique Almeida (2012)
This paper proposes a switched-capacitor converter to drive power light emitting diodes (LEDs). In contrast to conventional constant dc current drivers, the current pulse is provided by this switched-capacitor LED driver. In the present driver, the capacitor is charged and discharged through of the output circuit and the current flow direction is controlled by switch. Based on the charge control analysis, the effects of switching devices on the proposed converter are discriminated and evaluated. The experimental results demonstrated the technical feasibility of using the proposed converter for LEDs.